Nobelist TD LEE Scientist Cooperation Network and Scientist Innovation Ability Model - Jin-Qing Fang; Qiang Liu (Discrete Dynamics in Nature and Society)
Nobelist TD Lee scientist cooperation network (TDLSCN) and their innovation ability are studied. It is found that the TDLSCN not only has the common topological properties both of scale-free and small-world for a general scientist cooperation networks, but also appears the creation multiple-peak phenomenon for number of published paper with year evolution, which become Nobelist TD Lee’s significant mark distinguished from other scientists. This new phenomenon has not been revealed in the scientist cooperation networks before. To demonstrate and explain this new finding, we propose a theoretical model for a nature scientist and his/her team innovation ability. The theoretical results are consistent with the empirical studies very well. This research demonstrates that the model has a certain universality and can be extended to estimate innovation ability for any nature scientist and his/her team. It is a better method for evaluating scientist innovation ability and his/her team for the academic profession and is of application potential.